Parents' vaccination information seeking, satisfaction with and trust in medical providers in Switzerland: a mixed-methods study. Issue 2 (28th February 2022) - Ebi, Selina Jana; Deml, Michael J; Jafflin, Kristen; Buhl, Andrea; Engel, Rebecca; Picker, Julia; Häusler, Julia; Wingeier, Bernhard; Krüerke, Daniel; Huber, Benedikt M; Merten, Sonja; Tarr, Philip E
Abstract : Objectives: The aim of this study was to better understand parental trust in and satisfaction with information sources and medical providers regarding decision making about childhood vaccines. Setting: The study was part of a Swiss national research programme investigating vaccine hesitancy and underimmunisation. Participants: We conducted qualitative interviews with 37 providers and 30 parents, observed 34 vaccination consultations, and then conducted quantitative surveys with 130 providers (both complementary and alternative medicine (CAM) oriented and biomedically oriented) and 1390 parents. Main outcome measures: Participants' vaccination information sources used in their decision-making process, parents' trust in and satisfaction with these sources and providers. Results: Based on the Parent Attitudes about Childhood Vaccines scale, we considered 501 parents as vaccine-hesitant (VH) and 889 parents as non-VH. Whereas both groups mentioned providers as the most trusted source of information, VH-parents were less likely to mention paediatricians (N=358 (71%) vs N=755 (85%)) and public health authorities (N=101 (20%) vs N=333 (37%)) than non-VH-parents. VH-parents were more likely to have consulted another provider (N=196 (39%) vs N=173 (19%)) than non-VH-parents, to express less satisfaction with both their primary (N=342 (82%) vs N=586 (91%)) and other providers (N=82 (42%) vs N=142 (82%)) and less trust in their primary (N=368 (88%) vs N=632 (98%)) and other providers (N=108 (55%) vs N=146 (84%)). VH-parents were less likely to be satisfied with their biomedical primary provider than non-VH-parents (100 (69%) vs 467 (91%)). However, when the primary provider was CAM-oriented, there were similar levels of satisfaction among both groups (237 (89%) VH-parents vs 118 (89%) non-VH-parents). All differences were significant (p<0.05). Conclusions: While the provider remains the main information source, VH parents turn to additional sources and providers, which is likely related to VH parents being rather dissatisfied with and distrusting in obtained information and their provider. Ethics: The local ethics committee (Ethikkommission Nordwest- und Zentralschweiz, EKNZ; project ID number 2017-00725) approved the study.